(untitled) (Eureka Journal of Education & Learning Technologies, 2025)
Artificial Intelligence (AI) has revolutionized numerous global industries, and education is no exception. Within the domain of Teaching English as a Second Language (TESL), AI-driven technologies offer unprecedented opportunities for personalization, learner autonomy, multimodal engagement, and pedagogical innovation. This paper examines the influence of AI on ESL learning environments, focusing on instructional benefits, practical applications, limitations, ethical concerns, and future prospects. The analysis draws on current research, educational practices, and classroom trends to provide a comprehensive overview of how AI is shaping modern TESL methodologies